The efficiency of container terminal management system at Klang Port Management / Norsaniah Md Noh - Md Noh, Norsaniah (1999)
Information technology is developing rapidly. The development had influence for the port industry to develop the information technology in the industry. There are many information technology systems developed. One of the systems that had been developed is the Container terminal Management System (CTMS). During the usage of the system, the researcher hod found that there are some problems occur whereby it can affect the operation including, the performance. Namely the planning of yard, equipment and. manpower is the main problem whereby it can reduce the efficiency of the system. This must be taken into consideration by the management because if the shortcomings of the system are not handled, it will effect the organisation especially the operation of containerised goods. This will initially reduce the company's revenue